EFFECT OF IMAGERY PSYCHOLOGICAL SKILL TRAINING ON HANDBALL GAME PENALTY SHOOTING IN HAWASSA CITY ADMINISTRATION U-17 MALE HANDBALL PROJECT - Derar Tesfaye, Muluken (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2022)
Now a day’s handball becomes a tough and categorical sport requiring from players enviable physical, mental, and technical preparedness. Sport psychology has emerged as a field and similar to physical skills, psychological skills increase in physical performance and remove the negative issue. Athletes can use imagery skill to create or recreate an experience in their mind that seems real-life like. So it is important to investigate the effects of imagery skills training in handball game penalty shooting. A total of 30 Hawassa city administration U-17 male handball project players and a coach were selected as participants of the study. Pre and post training test was conducted to measure the variables of the study and the data were collected by using multiple methods. All the selected subjects participated in the designed imagery skills program for consecutive twelve weeks, three days per week and for 15 minutes per day. The data were analyzed using paired-t test and independent sample test with the level of significance at 0.05 by SPSS version 20. After the twelve weeks training, the significant improvement was observed on posttest of experimental group. The result indicates that the mean difference value of paired test of pre and posttest was 1.96 and independent sample test was 3.6. The mean result of experimental group in pretest was 9.06 ± 0.79, whereas12.86 ± 0.63 posttest; it shows a 3.8 difference on experimental group of the study. This result indicates that the effective change was observed on experimental group than control group. Based on the findings of this study, I recommend that applying imagery, as part of the training, at different level plays a vital role for the success of the team